Opportunities and Challenges For Developing Cross-Border Tourism On The Indonesia - Malaysia Border In Sambas District, West Kalimantan Province - Desi Yuniarti; Muslimin H Kara; Abdul Wahid Haddade; Wulan Purnamasari (SOUTHEAST ASIA JOURNAL oF GRADUATE OF ISLAMIC BUSINESS AND ECONOMICS, 2025)
This study analyzes the development of Cross-Border Tourism in the Indonesia-Malaysia border region in Sambas Regency, West Kalimantan, in the perspective of Islamic Economics. The study focuses on the development patterns, opportunities, and challenges faced in the management of cross-border tourism. This research is descriptive qualitative with normative, conceptual, and comparative approaches, involving an analysis of the provisions of the Qur'an, Hadith, tourism theory, as well as a comparison of Cross-Border Tourism models. The results show that the development of cross-border tourism in Sambas Regency has significant potential in increasing tourist attraction and strengthening cross-border economic relations. The implementation of sharia principles, such as the provision of a Muslim-friendly environment, adequate access to worship, halal products, and sharia-based services, is an important factor in optimizing this potential. Despite the great opportunities, the main challenges include sub-optimal infrastructure, cross-border regulations, and synergy between stakeholders. Therefore, a sharia-based development strategy is needed to create sustainable and competitive tourism, while supporting inclusive regional economic development.